PHƯƠNG TRÌNH TỈ LƯỢNG HÓA HỌC TRONG NGHIÊN CỨU THỰC NGHIỆM ĐỘNG HỌC PHẢN ỨNG - Anh, Phạm Ngọc; Tiến, Vũ Đình; Bằng, Nguyễn Công; Kỳ, Mai Xuân (Vietnam Journal of Science and Technology, 2012)
APPLICATION OF STOICHIOMETRIC EQUATIONS SYSTEM TO INVESTIGATE EXPERIMENTALLY REACTION KINETICS Kinetics of the chemical conversion of carbon used H2O và CO2 was experimentally investigated. Due to analytical abilities, CO and CO2 were chosen as key components. Based on establishing and solving stoichiometric equations, the mass variations of all components in the system were estimated. It allows determining the experimental parameters to give a kinetics description of the reactions.